Ecosystem Damage Due to Weaknesses in Wildlife Protection Regulations - Setyani, Erlin; Octwelfth, Florentina Ezrahi; Ranti, Gabriella; Mambo Jr, Glen Clifford; Jasmine, Aldizya; Putra, Muhammad Rangga Arya; Fahlevi, Fiqih; Hitiyahubessy, Jeanifersu (CV. Rayyan Dwi Bharata, 2025)
The diversity of Indonesia's fauna and flora is quite enormous. Its strategic geographical location makes Indonesia a suitable place for breeding, and creates a good ecosystem for the wildlife species that live in it. However, the diversity and uniqueness of nature and animals are not well supported and protected, especially by irresponsible humans and weak regulations. Environmental conservation and sustainable management of natural resources can be used as the purpose of the juridical foundation to strengthen and clarify the legislation itself, so that there is no legal vacuum or “elastic law” that has no clear benchmark. Therefore, in this research, the community and regulators need to see the internal and external challenges in facing the problems faced by Mother Nature and the ecosystems and animals in it. In this article, the method used is a qualitative descriptive approach and a literature study that becomes the author's reference.